PENGARUH LATIHAN ZIG-ZAG TERHADAP PENINGKATAN KECEPATAN DAN KELINCAHAN ATLET FUTSAL VAMOS ACADEMY PADANG - M.Yusuf Sulaiman; Ridho Bahtra; Andri Gemaini; Ilham (Jurnal IKEOR, 2024)
The issue in this study is the still low degree of deftness and speed of Futsal competitors Vamos Foundation Padang. This study sought to determine whether Futsal athletes at Vamos Academy Padang’s improved agility and speed were aided by zig-zag run training. A quasi-experimental study is this kind of research. This exploration was led in June to July 2024 at Brilliance Futsal, GOR H. Complex of Agus Salim Padang in Padang City, West Sumatra The participants in this study were all 22 Padang Futsal athletes from Vamos Academy. The total sampling method was used for the sampling, so there were 22 athletes included in the study. The instruments in this review were 1) deftness utilizing the Illinois dexterity test and 2) speed utilizing the 20-meter run. The information investigation strategy utilized factual examination of the mean contrast test or t-test. 1) This study found that futsal athletes from the Vamos Academy Padang Team’s agility increased by 0.84 points on average when they participated in zigzag run training, with a t-value of 10.94 > 1.72. 2) There is an impact of crisscross run preparing on the speed capacity of futsal competitors of the Vamos Foundation Padang Group with a t count of 9.69> t count of 1.72 where there is a typical expansion in the normal readiness of 0.22 places.